Kemampuan Berpikir Aljabar Siswa SMP dalam Menyelesaikan Masalah Relasi dan Fungsi Ditinjau dari Perbedaan Jenis Kelamin - Alvira Ramanda; Endah Budi Rahaju (MATHEdunesa, 2024)
Algebraic thinking is a mental activity that occurs within a person in using symbols, generalizing, formulating relationships between patterns and developing variable concepts in problem solving. This study aims to describe the algebraic thinking ability of junior high school students with male and female gender in solving relation and function problems. Researchers conducted an algebraic thinking ability test on two junior high school students in Surabaya with high mathematics ability based on the results of the mathematics ability test. The results showed that male and female students on the generalization indicator, can find information contained in the relation and function problems, and identify patterns based on the objects given systematically. Likewise, on the abstraction indicator, both students can express something that has no known value in algebraic form and make equations from the relationship between the objects given. In the dynamic thinking indicator, male and female students can predict the relationship between known values to determine the next value, but only female student can solve with two different alternative ways. On the organization indicator, male student can arrange the information obtained into a logical deduction strategy, while female student arrange the information in the form of a graph but are less precise to describe the problem situation and the relationship between the conditions of the overall problem. On the modeling indicator, only male student can state the problem into a mathematical model. Therefore, this research can be used as a consideration for teachers to familiarize students to find other ways of solving so that students will be skilled in thinking algebra by paying attention to differences in the algebraic thinking abilities of male and female students. In addition, further research needs to be done to examine subjects of moderate or low mathematical ability, to see differences in students' algebraic thinking skills because there may be differences in algebraic thinking skills between male and female students with moderate or low ability.